Developmental Enhancement and Application of a Low-Cost Educational Robotics Kit: A Case Study Validation with a University Competition - Dantas, Igor Matias de Lima; Santana Junior, Orivaldo Vieira de; Alves, Karina Messias da Silva; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This paper presents the latest developmental im-provements done on the URA low-cost robotic kit, which uses a open-source and low-cost robotics paradigm and was designed for general activities in educational robotics. Our kit is planned with the aim of facilitating the teaching of the basic concepts of programming, electronics, and mechanics. The current version (9.0) was redesigned with a focus on accessibility and intuitiveness in order to meet the demands of practical training in the educational context with limited infrastructure. The validation of the developments occurred in a mini-robotics competition held at the School of Science and Technology of the Federal University of Rio Grande do Norte, where freshmen undergraduate students assembled a robot with the kit and faced challenges inspired by the Brazilian Robotics Olympiad (OBR). The results pointed to the effectiveness of the kit in forming student teams, as well as its potential for replication in public schools and robotic events. This paper contributes with the development stages, the components, a simulation software, and programming methodology, pointing out the main difficulties encountered during implementation.